New species and records of the genera Scutacarus and Imparipes (Acari: Heterostigmatina: Scutacaridae) associated with Coleoptera and Hymenoptera (Arthropoda: Insecta) from Iran - Navabi, Amin; Hajiqanbar, Hamidreza; Mortazavi, Abdolazim (Zootaxa, 2018)
A survey was carried out to study scutacarid mites (Acari: Prostigmata: Scutacaridae) associated with insects in Borujerd city, western Iran. A new species and six species new to the mite fauna of Iran, and mostly new to Asia, were found. Scutacarus pseudoapodemi Navabi & Hajiqanbar sp. nov. phoretic on the ant Camponotus oasium Forel (Hymenoptera: Formicidae) is described and illustrated. The new records of scutacarids associated with ants and beetles are: Scutacarus avarus Khaustov, 2008; Imparipes ignotus Khaustov & Chydyrov, 2004; I. gagati Khaustov, 2008; I. malus Khaustov, 2008 and I. morosus Khaustov, 2008 associated with various ants, and I. moderatus Khaustov, 2008 associated with the beetle Drasterius bimaculatus (Rossi) (Coleoptera: Elateridae). New host records are documented and the world distribution of these mites is also reviewed.